Seletividade de herbicidas aplicados em pré-emergência e pós-emergência sobre Crotalaria ochroleuca, Cajanus cajan e Raphanus sativus - Pereira, Laís Molinari (Universidade Federal de São Carlos, 2017)
Green manure has been widely diffused because of the benefits it brings to the chemical, physical and biological characteristics of the soil. However, the adoption of this practice by farmers depends on the definition of management strategies that allow the full development of these crops in the field. Among the strategies, the definition of selective herbicides is a fundamental point in helping the development of the crop. The objective of this work was to evaluate in the greenhouse if pre-emergence and post emergence herbicides are selective for the three green manure species: forage turnip (Raphanus sativus L. cv. CATI AL 1000), dwarf pigeon pea (Cajanus Cajan (L) Millsp cv. IAPAR 43) and crotalaria (Crotalaria ochroleuca L. comun cv.). In the field evaluate if the herbicides defined as selective in greenhouse will damage crops, in relation to phytomass production. The herbicides applied in greenhouses in pre-emergence were atrazine, saflufenacil, sulfentrazone and metribuzin. Separately, post-emergence bentazon, fluazifop-p-butyl, fomesafem, chlorimuron ethyl, mesotrione, imazethapyr, nicosulfuron, clomazone and imazapique. The doses were 0.5, 0.75, 1 and 1.25 of the commercial dose. The three species of green manure were planted in cups with a capacity of 0.5 L. The application of pre-emergence herbicides was performed one day after sowing, and the post-emergence herbicides were applied when the plants had 2 to 3 Pairs of definitive leaves. Phytotoxicity evaluations were performed at 7, 14, 21 and 28 days post-emergence (DAE) for pre-emergent herbicides and 7, 14, 21 and 28 days after application (DAA) for post-emergence herbicides. At 28 DAE / DAA the aerial part of the plants were collected to determine the dry biomass. In greenhouse the herbicides considered selective for Cajanus cajan were fluazifop-p-butyl, bentazon, imazethapyr, clomazone, imazapique, mesotrione and nicosulfuron. For Crotalaria ochroleuca: fluazifop-p-butyl, imazethapyr, bentazon, clomazone, fomesafem and mesotrione. No herbicide was selective for Raphanus sativus. In the field experiment were used the herbicides that were selective in the greenhouse, in the case only for the crotalaria and dwarf pigeon pea. The experimental design was a randomized block design with 4 replicates for treatments and controls. When the crotalaria plants were with up to 3 pairs of true leaves were sprayed with the herbicides bentazon, fluazifopp-butyl, fomesafem, mesotrione, clomazone and imazethapyr. The application in pigeon pea occurred at the same phenological stage with the herbicides bentazon, fluazifop-p-butyl, mesotrione, imazethapyr, nicosulfuron, clomazone and imazapique. Phytotoxicity of the crops was evaluated weekly until flowering corresponding to 42 DAA for pigeon pea and 56 DAA for sunflower. In the field only the mesotrione in the crotalaria crop caused 100% of phytotoxicity, in the other treatments all herbicides selected in greenhouse were also selective in the field, allowing the complete cycle of the crop and producing significant biomass
Selectivity of pre-emergency and post-emergency applied herbicides about Crotalaria ochroleuca, Cajanus cajan and Raphanus sativus
Keywords: Fitotoxicidade; Adubação verde; Leguminosas; Fabaceae; Brassicaceae; Phytotoxicity; Green manuring; Legumes; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS